PREVALENCE OF ECTOPARASITE TICK AND MITE INFESTATION ON DOMESTIC CHICKEN IN BALI - Hesty Kartika Tandisalla; Ida Bagus Made Oka; I Made Dwinata (Buletin Veteriner Udayana, 2024)
The raising of free-range chickens is generally intended as laying hens, broilers, and pets by the people of Indonesia. One of the common diseases affecting free-range chickens is the infestation of ectoparasites ticks and mites that can interfere with the health of chickens and even cause economic losses on a farm. The aim of this study was to determine the prevalence of ectoparasite infestation of ticks and mites and to identify the types of ticks and mites that infest free-range chickens in Bali. The objects in this study were tick and mite ectoparasites that infested 5-6 month-old of 60 free-range chickens. Ticks ectoparasites were taken directly one by one using tweezers and for non-scabies mites were observed using a magnifying glass and taken using cotton wool soaked in 70% alcohol. Each ectoparasite taken from one individual chicken was put into an eppendorf tube filled with 70% alcohol. Identification was done by examining the preparations using a light microscope based on the CDC identification key (1966). The results of this study showed that the prevalence of ectoparasites in free-range chickens in Bali was 78% with a prevalence of ticks at 32% and a prevalence of mites at 78%. The types of ticks found were Haemaphysalis spp. and Megninia ginglymura mites. Further research is needed to identify the types of ectoparasites ticks and mites that infest chickens in Indonesia.